Peran Mahasiswa Kampus Mengajar dalam Meningkatkan Literasi Siswa SMP Negeri 15 Bengkulu Tengah - Kholifah Sugiyanti; Rizki Pratama; Rina Yuniarti (GHAITSA : Islamic Education Journal, 2024)
The Teaching Campus aims to improve the quality of education in Indonesia where one of the work programs carried out is to increase literacy which is important knowledge to be mastered by elementary school students in order to succeed in education and daily life. This study aimsto analyze efforts to improve the literacy of SMP N 15 Bengkulu Tengah students through an effective approach, this study was conducted by involving grade 7 and 8 students of SMP N 15 Bengkulu Tengah whose literacy level is still low. The method used is qualitative descriptive with the object of using interesting reading books, project-based teaching, and the use of technology in learning. The results showed that an approach involving interesting reading books was able to increase students' reading interest. In addition, creativity-based teaching allows students to develop critical and problem-solving skills, while the use of technology provides wider access to learning resources, this research makes an important contribution to improving the literacy of SMP N 15 students. The results suggest that diverse and innovative approaches can increase students' interest in reading and their overall literacy skills.